Analysis of Learning Difficulties in Simple Fractions through Elementary School Class VI Fractional Card Media : Analisis Kesulitan Belajar Matematika Pada Materi Pecahan Sederhana Melalui Media Kartu Pecahan Di Kelas VI SD - Mila Wati Dalimunthe; Chairunnisa Amelia (ITScience (Information Technology and Science), 2025)
This study aims to analyze the difficulties in learning mathematics in simple fraction materials experienced by grade VI students at Nida Suksasat School Elementary School, Satun, Thailand, and to explore the effectiveness of using fractional card media in overcoming these difficulties. This study uses a case study approach with 30 grade VI students who have difficulty understanding the concept of simple fractions. Data were collected through observation, interviews, and tests before and after using fractional card media. The results show that students' main difficulties are understanding the concept of dividing equal parts in fractions and performing mathematical operations such as addition and subtraction of fractions. Using fractional card media has proven to be effective in helping students visualize the concept of fractions and improve their understanding. This media also helps students understand the relationship between parts and the whole, making solving fractional problems easier. This study suggests that fractional card media is used regularly in mathematics learning to reduce learning difficulties in simple fractional material in grade VI of Elementary School. Most students have difficulty understanding simple fraction material, especially in recognizing the concept of fractions, performing basic operations such as addition and subtraction of fractions, and simplifying fractions. Students also have difficulty understanding the relationship between fractions, decimals, and percents.